2022
DOI: 10.1093/eurheartj/ehac544.3018
|View full text |Cite
|
Sign up to set email alerts
|

Long non-coding RNA TERRA regulates DNA damage and survival of endothelial cells and cardiomyocytes: implications for aging

Abstract: Introduction Ageing is the major risk factor for cardiovascular disease. Long non-coding RNAs are emerging as novel regulators of cellular functions and contributors to cardiovascular ageing. One of the hallmarks of aging is telomere attrition. Non-coding transcripts called Telomeric repeat-containing RNA (TERRA) are molecules of 0.2–10kb in length which are transcribed from the subtelomeres and telomeres of chromosomes and might play a role in cardiovascular ageing. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…The pathological consequences of these DNA-damaging mechanisms are often associated with vascular disease, especially atherosclerosis. Some studies have identified specific lncRNAs as regulators of DNA damage responses [15, [23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…The pathological consequences of these DNA-damaging mechanisms are often associated with vascular disease, especially atherosclerosis. Some studies have identified specific lncRNAs as regulators of DNA damage responses [15, [23][24][25].…”
Section: Introductionmentioning
confidence: 99%